2021
DOI: 10.3389/fcell.2021.690522
|View full text |Cite
|
Sign up to set email alerts
|

X-Inactive-Specific Transcript: Review of Its Functions in the Carcinogenesis

Abstract: X-inactive–specific transcript (XIST) is one of the firstly discovered long non-coding RNAs with prominent roles in the process of X inactivation. Moreover, this transcript contributes in the carcinogenic process in different tissues. In addition to interacting with chromatin modifying molecules, XIST can be served as a molecular sponge for miRNAs to modulate expression of miRNA targets. Most of the studies have indicated an oncogenic role for XIST. However, in prostate cancer, a single study has indicated a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 116 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…However, whether it is an oncogene or a tumor suppressor gene is not clear, and both sides has supporting reports. Even in the same tumor, there are inconsistent research results, including hepatocellular carcinoma, breast cancer, ovarian cancer and renal cell carcinoma [ 15 ]. This phenomenon also exists for osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whether it is an oncogene or a tumor suppressor gene is not clear, and both sides has supporting reports. Even in the same tumor, there are inconsistent research results, including hepatocellular carcinoma, breast cancer, ovarian cancer and renal cell carcinoma [ 15 ]. This phenomenon also exists for osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the function of XIST mainly includes binding chromatin modifying molecules and binding miRNAs as molecular sponges to regulate the expression of target molecules [ 15 ]. We found that XIST was mainly localized in the cytoplasm of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…XIST/miR-140, miR-124/iASPP LncRNA X inactivation-specific transcript (XIST) is derived from XIST gene and is important for inactivation of X chromosome in the development of female mammals (94). It is reported that XIST is dysregulated in a variety of cancers and exerts its either tumor-suppressive or oncogenic role in tumorigenesis and progression of cancers, such as hepatocellular carcinoma, lung cancer, gastric cancer, and osteosarcoma (95)(96)(97). Recent studies indicated that XIST was overexpressed in PC and involved in regulating the cell proliferation, apoptosis, migration, and invasion (98).…”
Section: Hotair/mir-613/notch3mentioning
confidence: 99%
“…However, in late stage breast tumors or established BC cell lines, the Xi, or Barr body, is commonly absent, presumably due to the loss of Xi and replication of the active X chromosome (Xa) [24] and/or epigenetic erosion of the Xi [25], leading to the formation of XIST clouds in the nucleus de cient in XCI [26]. Supporting this abnormal function of XIST in post-XCI tumor cells, XIST expression in a wide variety of cancer cells suppresses or promotes tumor growth and/or metastasis [27][28][29]. Such divergent roles of XIST in cancer development and progression may re ect the fact that XIST functions as a major molecular sponge to repress a plethora of oncogenic or tumor suppressive MicroRNAs (miRNAs) and lncRNAs, leading to suppression or promotion of tumor growth and metastatic progression in a highly context-dependent manner [27][28][29].…”
Section: Introductionmentioning
confidence: 99%